Quantifying Spatial Variability of Available Zinc in Alluvial Soils of Brahmaputra Plains, India - D. Dutta, S. Bandyopadhyay; A.K. Sahoo, S.K. Reza*, U. Baruah, S. Mukhopadhyay (Journal of the Indian Society of Soil Science, 2021)
Occurrence of zinc (Zn) deficiency in soils and plants has been accounted for worldwide including northeastern India. The present study was conducted to determine the spatial distribution and degree of risk of Zn deficiency in Brahmaputra plains of northeastern India using statistics and geostatistics. With the help of handheld global positioning system (GPS), 5494 soil samples were collected using 1 km Ã— 1 km grid at 0-25 cm depth from three districts of Assam state of India namely, Tinsukia, Morigaon and Nalbari representing upper Brahmaputra valley zone (UBVZ), central Brahmaputra valley zone (CBVZ) and lower Brahmaputra valley zone (LBVZ) covering 6249 km2 area and analyzed for pH, organic carbon (OC) and Zn. Dataset was normally distributed. Geostatistical analyses were carried out, including experimental variogram and model fitting. Analysis of the isotropic variograms indicates that the range values of 3900, 4400 and 5800 m for UBVZ, CBVZ and LBVZ, respectively. It implies that the length of the spatial autocorrelation was much longer than the sampling interval of 1 km. The nugget/sill ratio was 0.506, 0.859 and 0.589 for UBVZ, CBVZ and LBVZ, respectively and it indicates moderate spatial dependence. Further, with the ordinary kriging, spatial distribution map showed that the Zn is deficient for plants in the all the three zones of Brahmaputra plains. The probability map produced based on indicator kriging showed that Zn deficiency was noticed in 34% of crops grown area of the Tinsukia, 70% crops grown area in Morigaon and 85% of crops grown area in Nalbari districts. The correlation analysis showed that Zn was significantly and positively correlated with OC and significantly and negatively with pH in Brahmaputra plains. Thus, the present study is of immense help to minimize both yield loss and environmental threats of Zn toxicity due to under or overdose of Zn fertilizer application in Brahmaputra plains of northeastern India.